2015
DOI: 10.12707/riv14030
|View full text |Cite
|
Sign up to set email alerts
|

Depression in the elderly: symptoms in institutionalised and non-institutionalised individuals

Abstract: Enquadramento: As perturbações psiquiátricas no idoso são comuns e responsáveis pela perda de autonomia, pelo agravamento de quadros patológicos preexistentes e pela neglicência no auto cuidado. Objetivos: O presente trabalho pretende estudar a associação entre a institucionalização e a presença de depressão em idosos. Metodologia: Foi desenvolvido um estudo transversal, realizado num grupo de idosos com mais de 65 anos, a quem foi aplicada a Escala de Depressão Geriátrica (EDG). Resultados: Foram estudados 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 8 publications
1
14
0
3
Order By: Relevance
“…Studies have indicated that the elderly population in general live without partners 25 while a study in Paraná found that approximately 34% of respondents were widowed 26 . At the age of 80 years old or more, this figure rises to approximately 63%7, 13,27 . It has been found that when facing widowhood women are less likely than men to seek a new relationship 26 .…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Studies have indicated that the elderly population in general live without partners 25 while a study in Paraná found that approximately 34% of respondents were widowed 26 . At the age of 80 years old or more, this figure rises to approximately 63%7, 13,27 . It has been found that when facing widowhood women are less likely than men to seek a new relationship 26 .…”
Section: Discussionmentioning
confidence: 94%
“…In studies aimed at this population group, samples formed only of women are common, and when samples are mixed, the number of women frequently exceeds the number of men 4,7,11,13 . These findings reinforce the fact that on average women live longer than men and that more women attend specific programs specifically aimed at the elderly 2,[11][12][13][14][15]24 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations